2009
DOI: 10.1007/s00464-009-0499-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic distal pancreatectomy: critical analysis of preliminary experience from a tertiary referral centre

Abstract: Laparoscopic distal pancreatic resection is feasible, safe, and efficient. However, this surgery should only be performed in specialized centres with extensive experience in pancreatic and laparoscopic surgery. Oversewing the pancreatic stump after transaction with Endostapler may reduce the incidence of pancreatic leak. Centralization of pancreatic surgery has a positive impact on building up surgical expertise, resulting in obvious benefits for both patients and institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…To date, most reports of laparoscopic distal pancreatectomy are small series from single institutions. [33][34][35][36][37][38] The occurrence of pancreatic fistula following laparoscopic distal pancreatectomy in these studies has been reported as ranging from 13-50%. 39 In our series, laparoscopic distal pancreatectomy was attempted in 16 patients and completed in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most reports of laparoscopic distal pancreatectomy are small series from single institutions. [33][34][35][36][37][38] The occurrence of pancreatic fistula following laparoscopic distal pancreatectomy in these studies has been reported as ranging from 13-50%. 39 In our series, laparoscopic distal pancreatectomy was attempted in 16 patients and completed in 13 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The technique for LDP has been described elsewhere (Abu Hilal et al, 2009). In short, five ports (three 5-mm ports and two 10/12-mm ports) were used.…”
Section: Ldpmentioning
confidence: 99%
“…It is not necessary for the surgeon's hand to feel the borders of the lesion. Most authors advocate the use of intraoperative laparoscopic ultrasound to localize the lesion and define the extent of the resection (30). If the lesion is obvious, dissection is initiated by mobilizing the lower pancreatic margin 2 cm proximal to the lesion.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…With increasing experience and specialized centers, the conversion rates are expected to decrease. The most common reasons for conversion are obesity, dense omental fat, intraoperative bleeding, malignant disease requiring lymph node dissection, inability to detect the tumor, bulky tumors, and peritoneal adhesions due to previous surgery (30).…”
Section: Surgical Techniquesmentioning
confidence: 99%